2012
DOI: 10.1007/s12017-012-8192-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Phosphocholine Containing Brain Lipids in Mice with Sensorimotor Deficits and Anxiety-Like Features After Exposure to Gulf War Agents

Abstract: The central nervous system (CNS)-based symptoms of Gulf War Illness (GWI) include motor dysfunction, anxiety, and cognitive impairment. Gulf War (GW) agents, such as pyridostigmine bromide (PB), permethrin (PER), N,N-diethyl-meta-toluamide (DEET), and stress, are among the contributory factors to the pathobiology of GWI. This study characterizes disturbances in phosphocholine-containing lipids that accompany neurobehavioral and neuropathological features associated with GW agent exposure. Exposed mice received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 44 publications
8
60
1
Order By: Relevance
“…further showed that PM and DEET (but not PB) exposure can greatly inhibit the proliferation of NSCs. Interestingly, cognitive dysfunction observed in this rat model contrasts with a recent study in C57BL/6 mouse model where exposure to similar doses of chemicals and stress did not impair cognitive function but enhanced anxiety when examined 20 days after the exposure (Abdullah et al, 2012). The discrepancy between the two studies likely reflects differences in animal species and timing of behavioral analyses.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…further showed that PM and DEET (but not PB) exposure can greatly inhibit the proliferation of NSCs. Interestingly, cognitive dysfunction observed in this rat model contrasts with a recent study in C57BL/6 mouse model where exposure to similar doses of chemicals and stress did not impair cognitive function but enhanced anxiety when examined 20 days after the exposure (Abdullah et al, 2012). The discrepancy between the two studies likely reflects differences in animal species and timing of behavioral analyses.…”
Section: Discussioncontrasting
confidence: 85%
“…Additional factors may also be involved. For example, a recent lipidomics study reported that regulation of acetylcholine regulator and signaling pathways undergo alterations with exposure to GWIR chemicals (Abdullah et al, 2012).…”
Section: Other Factors Contributing To Gwir Chemical-mediated Hippocamentioning
confidence: 99%
“…The Folch extraction of serum and plasma samples was performed as previously described [66-68] using the Folch method [69] following an addition of di-14:0 fatty acid (FA) containing PC and PE (Matreya, Pleasant Gap, PA), di-16:0 PI, and 14:0 LPC (Avanti, Albaster, AL) as internal standards. High-pressure liquid chromatography (HPLC) was achieved using a 1mm ID x 10 cm column containing Pinnacle II 3 μm silica particles (Restek, Bellefonte, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This test was performed as described elsewhere (25,26). Mice were allowed to acclimate to the experimental paradigm using a single trial at 5 rpm fixed speed over 5 min.…”
Section: Rotarodmentioning
confidence: 99%
“…For these analyses, each mouse was a random factor, and exposure and time (days) were fixed factors. As described previously (26), for lipidomics, dimension reduction and multicolinearity issues were resolved using principal component analysis (PCA). Each component was extracted using the Anderson-Rubin method and examined as an outcome measure using MLM while adjusting for fixed (injury and technical replication) and random (mouse) factors.…”
Section: Statistical Analysesmentioning
confidence: 99%